Alterações fisiológicas em juvenis de Pacamã (Lophiosilurus alexandri) submetidos a hipóxia - Lívia de Assis Porto (2020)
The aim of this study was to evaluate the blood gasometric, hematological and biochemical responses of juveniles of L. alexandri submitted to hypoxia and subsequent recovery from hypoxia. 48 pacamã juveniles (360 ± 141.6 g and 26.6 ± 3.0 cm) were distributed and acclimated for 15 days in eight 120 L tanks in a water recirculation system (temperature 28.9 ± 0.28 °C, dissolved oxygen (OD) 5.10 ± 0.56 mg L-1 and total ammonia 0.05 ± 0.01 mg L-1). The fish were fed ad libitum, twice a day, with a commercial diet. The control group corresponds to fish subjected to continuous oxygenation for 96 h (OD - 5.6 ± 0.31 mg L-1) and the group in hypoxia to fish subjected to hypoxia (2.12 ± 0.90 mg L-1) for 48 h and later recovery to oxygenation conditions (5.30 ± 0.47 mg L-1) for another 48 h, totaling 96 h. Collections were performed at times of 24 and 48 h of hypoxia and 24 and 48 h of recovery. All data were subjected to two-way ANOVA statistical analysis followed by the Tukey’s test (P<0.05). There was no mortality during the experimental period. With regard to blood gasometric parameters, a higher pH was found at 24 h of recovery from hypoxia, when compared to the control group (P<0.05). For PvCO2 over time, significant differences were observed only in the group submitted to hypoxia, with a lower PvCO2 value at 24 h of recovery and a higher value at 48 h of recovery (P<0.05). Regarding oxygen saturation (sO2), significant differences were observed only at 24 hours of recovery, in which there was an increase in this variable in the hypoxia group when compared to the control group (P<0.05). There were no significant differences for lactate (cLac) and electrolytes K+, Na+, Cl-, Ca2+ and HCO3- (P>0.05). However, there was an increase in stHCO3- at 24 h of hypoxia, compared to the control (P<0.05). Base excess (BE) showed variations in the hypoxia group, with greater value at 24 h of hypoxia and at 48 h of recovery compared to the control (P<0.05). For hematological variables, there was an increase in hematocrit at 24 h of hypoxia compared to the control group (P<0.05). However, the values were similar to the control at 48 h of hypoxia, thus remaining in recovery (P>0.05). The lowest erythrocyte count was recorded at 48 h of hypoxia (P<0.05). Regarding the total number of leukocytes at 24 h of recovery, there was an increase in leukocyte count in the hypoxia group compared to the control group (P<0.05). Hemoglobin values remained constant in each group throughout the sampling times and also between groups at different sampling times (P>0.05). For biochemical variables, there was a decrease in glucose levels at 48 h of hypoxia and at 24 h of recovery, compared to the control group (P<0.05). Triglyceride levels varied over the sampling times in the control group, with the lowest values at 24 h hypoxia and 24 h recovery (P<0.05). Cholesterol and plasma protein did not differ between treatments at different collection times and within each group over time (P>0.05). The results presented for blood gasometric, hematological and biochemical parameters in this study show that juveniles of Lophiosilurus alexandri adapt well to low concentrations of oxygen dissolved in water for 48 h, without present mortality, adjusting their physiological variables to survive in this stress condition and returning normal conditions after 48 h of recovery from hypoxia.